2017
DOI: 10.1051/epjconf/201714101011
|View full text |Cite
|
Sign up to set email alerts
|

Fractal aspects of hadrons

Abstract: Abstract. The non extensive aspects of p T distributions obtained in high energy collisions are discussed in relation to possible fractal structure in hadrons, in the sense of the thermofractal structure recently introduced. The evidences of self-similarity in both theoretical and experimental works in High Energy and in Hadron Physics are discussed, to show that the idea of fractal structure of hadrons and fireballs have being under discussion for decades. The non extensive self-consistent thermodynamics and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Only recently has a connection between the experimental evidence of self-similarity in HEC and the Hagedorn and Frautschi models for fireball and hadrons been attempted [33,34] by introducing the concept of thermofractals; that is, systems with fractal structure in their thermodynamical quantities. It turns out that with such structure, Hagedorn's self-consistence principle can be rescued from its apparent failure, as discussed below.…”
Section: The Fractal Structure Of Hadronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently has a connection between the experimental evidence of self-similarity in HEC and the Hagedorn and Frautschi models for fireball and hadrons been attempted [33,34] by introducing the concept of thermofractals; that is, systems with fractal structure in their thermodynamical quantities. It turns out that with such structure, Hagedorn's self-consistence principle can be rescued from its apparent failure, as discussed below.…”
Section: The Fractal Structure Of Hadronsmentioning
confidence: 99%
“…Thermofractals are defined as systems in thermodynamical equilibrium presenting the following three properties [33,34]:…”
Section: Thermofractalsmentioning
confidence: 99%
“…The full understanding of the non-extensive statistics formulated by Tsallis, however, has not been accomplished yet. Four different connections between Boltzmann and Tsallis statistics have been proposed so far [8][9][10][11][12][13], all of them giving a clear meaning to the entropic index, q that appears in the non-extensive case and, in all connections, Boltzmann statistics are obtained as a special case. Nevertheless, it seems that the physical meaning of this parameter is not understood in the general case, and the difficulty to grasp the significance of the entropic index may be related to the fact that this quantity never appeared before in thermodynamics, while temperature, even if it appears as another parameter in statistical mechanics, had already an intuitive meaning in the description of thermodynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Deppman et. al [49] have shown that the fractal dimension of the thermofractal obtained from values of temperature and entropic index resulting from the analysis of p T distributions in high-energy interactions are similar to those found in analyses of intermittency in experimental data in high-energy collisions. Experimental data from 32 S-AgBr at 200 A GeV interaction has been analysed using the complex-network-based visibility graph method and the PSVG values obtained thereof have been compared for all the overlapping η-regions centered around c r , and it has been shown that the multiplicity fluctuation in high-energy interaction is self-similar and scale-free [30].…”
Section: Resultsmentioning
confidence: 54%